The Battle over Sunrise Rock: Examining the Constitutionality of Government Land Transfers to Private Entities - Pest, Michael (Journal of Law and Commerce, 2011)
Among the 1.6 million acres of southern California’s Mojave National Preserve stands a small cross, erected nearly a century ago as a memorial to veterans who died in World War I. Located in a remote site in the desert atop an outcropping known as Sunrise Rock, the cross, standing between five and eight feet tall,may appear to be of little significance to the average passerby. However, this seemingly inconsequential monument may have substantial implications for the federal government’s ability to transfer land to private entities. The location of the cross in the federally-owned Preserve has sparked widespread debate over whether it violates the First Amendment’s Establishment Clause, which guarantees that “Congress shall make no law respecting an establishment of religion.”The Establishment Clause is generally interpreted to guarantee citizens the right to be free from the government’s endorsement of a particular religion.Opponents of the cross have sought its removal for more than a decade, arguing that its location on the Preserve constitutes governmental endorsement of Christianity.